Effects of exemplar scenarios on public preferences for energy futures using the my2050 scenario-building tool - Demski, Christina; Spence, Alexa; Pidgeon, Nick (Nature Publishing Group, 2017)
Understanding which energy future configurations provide publicly acceptable levels of energy security, affordability, and environmental protection is critical for institutional decision-making. However, little is known about how scenarios influence energy preferences. Here we present nationally representative UK data on public preferences for energy futures using the my2050 scenario-building tool that encourages engagement with the holistic complexities of system change. Engagement with the tool strengthened existing preferences for renewable energy and intentions to take personal action. Importantly, patterns of energy preferences were influenced by exemplar scenarios, which served as reference points that anchored choices. Carbon capture and storage, nuclear power, biofuels, and changes to heating and travel were particularly impacted by scenarios indicating uncertainty and ambivalence regarding these options. Scenarios (and scenario-building tools) are valuable for engaging citizens about future energy systems. However, care is required in their design and interpretation to reach robust conclusions about underlying preferences and acceptance.